PREPOSITIONAL PHRASE AND ITS TRANSLATIONS FOUND IN THE NOVEL “BUDHA, A STORY OF ENLIGHTENMENT” - I Made Juliarta (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The novel